2022
DOI: 10.3389/fmicb.2022.898184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Parvovirus in Captive Siberian Tigers and Lions in Northeastern China From 2019 to 2021

Abstract: The fact that wild felines are carriers of pernicious infectious viruses should be a major concern due to the potential cross-species transmission between the felines and human or domestic animals. However, studies on the virus in the captive wild felines, especially in tigers, are thin on the ground. In this study, we screened four infectious viruses, namely, feline parvovirus (FPV), feline coronavirus (FCoV), canine distemper virus (CDV), and influenza A virus (IAV), in the blood samples of 285 captive Siber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…FPV, a member of the species Protoparvovirus carnivoran1 , is one of the fatal viral pathogens that can be cross-transmitted between domestic and wild carnivores, and FPV infection has been reported in various wild carnivores including Siberian tigers, threatening their survival [ 4 , 8 , 10 , 11 , 12 ]. In early May 2023, some Siberian tigers housed at Seoul Zoo showed clinical signs, such as depression, anorexia, vomiting, diarrhea, and epistaxis, and were suspected to be infected with a fatal enteric disease ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FPV, a member of the species Protoparvovirus carnivoran1 , is one of the fatal viral pathogens that can be cross-transmitted between domestic and wild carnivores, and FPV infection has been reported in various wild carnivores including Siberian tigers, threatening their survival [ 4 , 8 , 10 , 11 , 12 ]. In early May 2023, some Siberian tigers housed at Seoul Zoo showed clinical signs, such as depression, anorexia, vomiting, diarrhea, and epistaxis, and were suspected to be infected with a fatal enteric disease ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the qPCR assay used in this study was developed with the primers and probe set targeting the VP2 gene of all members of the Protoparvovirus carnivoran1 species including FPV, CPV-2, and its variants [ 13 ], further analyses were necessary to specify whether the detected virus was FPV or CPV-2. Indeed, previous reports have shown that tigers can be infected with genetically different parvoviruses, including FPV [ 8 , 10 , 11 , 25 ] and CPV-2a [ 4 , 26 ]. Therefore, to further characterize the detected KTPV-2305 strain, a complete VP2 gene sequence (GenBank accession number: OR365078) was obtained and analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly contagious, single-stranded DNA virus carnivore protoparvovirus 1 (hereafter parvovirus) can infect a wide range of carnivores and is divided into two main genogroups: the feline parvoviruses (formerly termed feline panleukopenia virus) and canine parvovirus 2 (CPV2) (Allison et al, 2013(Allison et al, , 2014. Both genogroups have been diagnosed in captive tigers (Steinel et al, 2000;Wang et al, 2019;Nur-Farahiyah et al, 2021;Huang et al, 2022), and CPV2 has been detected in tissues from a wild tiger in India (Shetty et al, 2020). The parvovirus genome is very small and lacks genes necessary for initiating viral replication, which is achieved through infection of rapidly dividing host cells (e.g., those found in developing fetuses or intestinal mucosa).…”
Section: Carnivore Protoparvovirusmentioning
confidence: 99%